“Chilling Effect” in the Judicial Decisions of the Polish Constitutional Tribunal as an Example of a Legal Transplant - Chybalski, Piotr (Review of European and Comparative Law, 2022)
The paper is dedicated to describing the way of reception by the Polish Constitutional Tribunal of the “chilling effect”, i.e. an institution related to such activities of public authorities that form an indirect act of deterrence regarding the execution of constitutionally guaranteed rights and freedoms, esp. the freedom of expression. The discussed concept has originated in judicial decisions of the US Supreme Court and has spread into many contemporary legal systems, including jurisprudence of the European Court of Human Rights. Although it is evident that the Tribunal “took over” that concept from the ECHR, it in fact developed its own, unfortunately internally inconsistent, understanding of the chilling effect. Four different ways of application of chilling effect may be noticed in judicial decisions of the Polish CT, while only two of them reflect the perception of this institution by the US Supreme Court and the ECHR.